Local repair procedure for carbon‐fiber‐reinforced plastics by refilling with a thermoset matrix. Issue 6 (19th October 2015) - Küchler, Kristin; Staiger, Elias; Hund, Rolf‐Dieter; Diestel, Olaf; Kirsten, Martin; Cherif, Chokri
ABSTRACT: Textile‐reinforced composites have given rise to an increasingly important key technology for lightweight construction in aerospace, automotive, civil engineering, and many other industries. Because there exists no suitable repair procedure for carbon‐fiber‐reinforced plastics (CFRPs), damaged parts have to be replaced completely; this is extremely disadvantageous both ecologically and economically. With fiber‐reinforced composites used being more and more often, fast and efficient methods for the local repair of damaged CFRPs are essential. In this article, a novel repair procedure for CFRP is presented. The thermal activation by IR radiation of oxide semiconductors was used to locally degrade the thermoset matrix of the damaged CFRP through the maintenance of its structural stability and properties. The matrix‐free textile structure was then refilled with a thermoset epoxy matrix. Carbon fibers from the treated area were characterized with scanning electron microscopy, IR spectroscopy, thermogravimetric analysis, and subsequently, tensile strength for single fibers to verify the effectiveness of the procedure. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 42964. Abstract :